(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article highlights the importance of cooperation between a practicing psychologist and parents in supporting students’ mastery of the educational process, taking into account their individual psychological characteristics and capabilities. It analyzes the effective use of psychological services within the education system and emphasizes the significance of collaboration with a teacher-psychologist in fostering positive psychological traits in a child’s development.